The Study on Utilization Waste Tire Seeds as Amixture of Ac-Wc Asphalt on Road Pavement - Fauzan Adzim; Zulkifli Lubis; Bobby Damara (Litbang Pemas - Universitas Islam Lamongan, 2021)
The purpose of this study are to find out the process of making AC-WC asphalt by using waste tire ore as an additives to hot mix asphalt and also to find out the general effect of waste tire ore as additives in the asphalt mixture to the characteristics of AC-WC asphalt. [2].In this study, the variation of the mixture added with tire ore starting from 0%, 3%, 6% and 8% addition of tire ore waste for the highest variation value is 3%, stability value is 494.99 kg, Voids Filled With Asphalt’s value is 68,40%, value of Voids in Mix is 3.65%, flow value is 3,21 %, value of Marshall Quotient is 154,61 kg/mm, Density’s value is 2,29 gr/cc. Finally, it was concluded that the addition of waste tire ore is not in accordance with SNI 06-2489-1991 because the higher percentage value in the mixture will decrease the value of Marshall Stability.